Epicardial Adipose Tissue and Postoperative Atrial Fibrillation - Petraglia, Laura; Conte, Maddalena; Comentale, Giuseppe; Cabaro, Serena; Campana, Pasquale; Russo, Carmela; Amaranto, Ilaria; Bruzzese, Dario; Formisano, Pietro; Pilato, Emanuele; Ferrara, Nicola; Leosco, Dario; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background. Atrial fibrillation (AF) often occurs after cardiac surgery and is associated with increased risk of stroke and mortality. Prior studies support the important role of inflammation in the pathogenesis of postoperative atrial fibrillation (POAF). It is known that an increased volume and a pro-inflammatory phenotype of epicardial adipose tissue (EAT) are both associated with AF onset in non surgical context. In the present study, we aim to evaluate whether also POAF occurrence may be triggered by an increased production of inflammatory mediators from EAT. Methods. The study population was composed of 105 patients, with no history of paroxysmal or permanent AF, undergoing elective cardiac surgery. After clinical evaluation, all patients performed an echocardiographic study including the measurement of EAT thickness. Serum samples and EAT biopsies were collected before surgery. Levels of 10 inflammatory cytokines were measured in serum and EAT conditioned media. After surgery, cardiac rhythm was monitored for 7 days. Results. Forty-four patients (41.3%) developed POAF. As regard to cardiovascular therapy, only statin use was significantly lower in POAF patients (65.1% vs. 84.7%; p-0.032). Levels of Monocyte Chemoattractant Protein-1 (MCP-1), in both serum and EAT, were significantly higher in POAF patients (130.1 pg/ml vs. 68.7 pg/ml; p=<0.001; 322.4 pg/ml vs. 153.4 pg/ml; p=0.028 respectively). EAT levels of IL-6 were significantly increased in POAF patients compared to those in sinus rhythm (SN) (126.3 pg/ml vs. 23 pg/ml; p=< 0.005). Conclusion Higher EAT levels of IL-6 and MCP-1 are significantly associated with the occurrence of POAF. Statin therapy seems to play a role in preventing POAF. These results might pave the way for a targeted use of these drugs in the perioperative period.